2012
DOI: 10.1007/s00508-012-0186-1
|View full text |Cite
|
Sign up to set email alerts
|

Strength of skeletal muscle and self-reported physical performance in Austrian glioblastoma-patients

Abstract: In this study, notable deficits especially in muscular strength of thigh muscles and general physical performance of patients with glioblastoma have been found before and after chemoradiation. Reduced muscle strength and impaired self-reported physical performance seem to be clinically relevant functional deficits in (Austrian) glioblastoma patients. Therefore, rehabilitation and supportive care should also include options to increase muscle strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The reporting of functional performance in studies of patients with glioma has almost exclusively used subjective measures as the Karnofsky Performance Status scale, although this scale is limited with low specificity and sensitivity to reporting changes [13]. Only a few studies of limited data material have used clinical outcome measures to evaluate the functional performance of patients with primary glioma [14][15][16][17][18][19][20][21][22][23]. It has yet to be investigated if laterality impact patients objectively measured functional performance, which might implicate differentiated rehabilitation interventions.…”
Section: Introductionmentioning
confidence: 99%
“…The reporting of functional performance in studies of patients with glioma has almost exclusively used subjective measures as the Karnofsky Performance Status scale, although this scale is limited with low specificity and sensitivity to reporting changes [13]. Only a few studies of limited data material have used clinical outcome measures to evaluate the functional performance of patients with primary glioma [14][15][16][17][18][19][20][21][22][23]. It has yet to be investigated if laterality impact patients objectively measured functional performance, which might implicate differentiated rehabilitation interventions.…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to tumour-associated thrombosis or embolism involving one of the deep penetrating arteries [ 73 ]. Keilani et al (2012) reported that patients with glioblastoma experienced deficits in the muscular strength of thigh muscles, and their general physical performance was lower than expected [ 15 ]. The deficits persisted in the post-operative period, which may be due to the impact of the clinical course of glioblastoma on patients’ muscular strength [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that brain tumours can have a significant impact on the functional connectivity of the brain and that different brain networks are affected in different ways depending on the type and location of the tumour [ 4 , 5 , 8 , 9 , 15 ]. This systematic review aims to evaluate the effects of tumour invasion on the cognitive function of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with GBM often receive high and extended doses of concomitant steroids that together with sedentary behaviour can affect clinical outcomes such as musculoskeletal atrophy, weakness, abnormalities in myofibrillar mass, mitochondrial volume, and capillary number, which may affect the ability to perform daily activities [28,29]. Decreased maximum muscle strength of knee extension has been observed in patients with gliomas to be lower than expected sex and age-matched comparisons [26,28]. Because resistance training is crucial to increasing muscle mass and preventing deterioration of functional performance it is indicated for patients with GBM.…”
Section: Resistance Trainingmentioning
confidence: 99%
“…However, performance status and age are among the best described prognostic factors in GBM, and most likely there is a strong relation between highperformance status and lower age [37]. Mean age in studies of patients with gliomas attending outpatient rehabilitation or physical capacity assessments ranges between 34 and 61 [7,26,28,38,39,40,41,42,43,44]. This implies that exercise rehabilitation intervention mainly addresses the younger population or patients with high Karnofsky performance status, which makes our case highly representative of this glioma population.…”
Section: Exercise Interventionmentioning
confidence: 99%